Secrets of the dragon tomb - Samphire, Patrick (Square Fish, 2017)
While dreaming of being a spy like those in his favorite magazine, twelve-year-old Edward has been stuck holding his eccentric family together but when his parents are kidnapped, he leads his sisters and cousin in an effort to rescue them across the danger-filled landscape of nineteenth-century Mars.